2018
DOI: 10.1108/jmtm-12-2016-0167
|View full text |Cite
|
Sign up to set email alerts
|

Observed difficulties during implementation of quality management systems in Brazilian manufacturing companies

Abstract: Purpose The purpose of this paper is to analyze the difficulties observed during implementation of quality management systems (QMSs) in Brazilian manufacturing companies. Design/methodology/approach The methodological strategy used was a literature review, a panel of experts and a survey. Through the literature review, 15 difficulties associated with the implementation of QMS were raised; these were organized into latent variables by specialists in the subject and served as the basis for a survey. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
10
0
3
Order By: Relevance
“…Siva et al (2016) also mention inappropriate timing and large differences in models that support standards. It is interesting to notice that several difficulties for IMS are also observed when companies are implementing QMS (Anholon et al, 2018). Rebelo et al (2015) also list the main problems observed during the integration process: (i) lack of human and material resources; (ii) resistance to change; (iii) complex organizational structure; (iv) diversity of products or services; (v) absence of a guideline to support the implementation process and absence of an explicit goal; (vi) lack of internal competence in system integration; (vii) lack of an international standard.Besides the above-mentioned difficulties, it is important to emphasize that a true integration of management systems provides several benefits, as discussed in the next section.…”
Section: Integrated Management Systemsmentioning
confidence: 99%
“…Siva et al (2016) also mention inappropriate timing and large differences in models that support standards. It is interesting to notice that several difficulties for IMS are also observed when companies are implementing QMS (Anholon et al, 2018). Rebelo et al (2015) also list the main problems observed during the integration process: (i) lack of human and material resources; (ii) resistance to change; (iii) complex organizational structure; (iv) diversity of products or services; (v) absence of a guideline to support the implementation process and absence of an explicit goal; (vi) lack of internal competence in system integration; (vii) lack of an international standard.Besides the above-mentioned difficulties, it is important to emphasize that a true integration of management systems provides several benefits, as discussed in the next section.…”
Section: Integrated Management Systemsmentioning
confidence: 99%
“…Looking at the health services sector, in addition to barriers that occur in other SME sectors, there are other obstacles: high employee turnover, resistance to change among employees, bureaucracy and hierarchical structure, professional autonomy, tensions between managers and professionals, and difficulties in evaluating health processes and outcomes (Alsughayir 2014;Mosadeghrad 2013). Some authors consider barriers to be difficulties and divide them into difficulties related to employees, difficulties associated with structuring the quality management system, integration difficulties, and difficulties arising from planning (Anholon et al,2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are different ways of assessing production systems in the literature, for instance, Anholon et al (2018) developed their study over implementation of quality management systems (QMS) in manufacturing companies, specific in Brazilian ones. In the applied method, 123 professionals of quality management participated in the research.…”
Section: Production Systemsmentioning
confidence: 99%